Displaced calcaneal fractures, midterm results of the sinus tarsi approach and screw fixation - Halwai, Manzoor Ahmad; Wani, Iftikhar Hussain; Gani, Naseemul; Farooq, Munir; Kutchay, Gulzar Ahmad; Bashir, Adil (International Journal of Research in Orthopaedics, 2019)
Background: We present the results of displaced intrarticular calcaneal fractures managed by limited sinus tarsi approach with good clinical and radiological outcome and less number of complications seen with conventional lateral approach. Methods: We operated 42 patients of displaced calcaneal fractures (Sanders type II and III) from April 2016 to March 2018 by open reduction and internal fixation with limited sinus tarsi approach by cannulated screws. All patients were evaluated clinically and radiologically before and after surgery. Final evaluation was done by Maryland Foot and Ankle score. Results: Patients were followed up for a mean period of 24 months. 30 patients returned to preinjury status activities while 12 patients confined themselves to sedentary schedule. The mean preoperative Bohler’s angle was 3.00 (range -30 to 20) while as mean postoperative Bohler’s angle was 26.4 (range 15 to 40). No wound dehiscence or skin necrosis was seen in our study. One patient developed superficial wound infection. Three patients reported prominent hardware related to screw heads. Four patients developed complex regional pain syndrome which was managed successfully at 6 month’s period. Conclusions: The limited sinus tarsi approach can be successfully used in displaced intra articular calcaneal fractures with good functional and radiological outcome. It allows good visualisation and reduction and can be used in patients with high risk. It is minimally invasive and undoubtly avoids the major soft tissue problems of extensile approach.